URANIUM DISTRIBUTION IN ORE-BEARING ROCKS OF THE MALINOV DEPOSIT: EVIDENCE FROM FISSION RADIOGRAPHY - Kondrat'eva I.A.; Maksimova I.G.; Nad''yarnykh G.I. (My University, 2004)
Application of f-radiography for the study of ore-bearing rocks of the Malinov uranium deposit revealed the following specific features: (1) occurrence of uranium in both authigenic and terrigenous components; (2) important role of fine–dispersed (mineral-free) mode of uranium occurrence; and (3) participation of different-aged epigenetic processes in the ore formation. The sequence of ore formation and transformation in this deposit is similar to that in the Semizbai deposit. Therefore, they can be united into a single subtype of Mesozoic infiltration deposits in western Siberia.